Effect of Cooking Time and Temperature on Extraction Yield and Antioxidant Properties of Beef Rendang - Nur Huwaidah Ithnin; Jinap Selamat; Suganya Murugesu; Peir Shinn Hew; Rashidah Sukor; Siti Nabilah Karim (USIM Press, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 9 No. 2 Page (106-111)